Sistem Informasi Laporan Kegiatan Harian Siswa Berbasis Android Di Sekolah Dasar Purba Adhi Suta Purbalingga - Anugrah Nur Ari Wibowo; Endang Setyawati; Sukata Sukata (Mahesa Research Institute, 2021)
Student daily activity records are kept as documentation tools to monitor the development of students' academic and non-academic abilities in capturing the learning process. The student's daily activity record is carried out by Purba Adhi Suta Elementary School. Purba Adhi Suta Elementary School is located in Purbalingga Regency which is located at Jalan Letnan Jenderal S.Parman Number 19 B Purbalingga. The obstacles faced by Purba Adhi Suta Elementary School in the form of the process of recording student activities are still done manually so that there is often a delay in managing the data of students' daily activity records and delays in the collection of student activity record recap books. The software development method used is a prototype. In this method the steps taken are the identification of user needs, making prototypes, adjusting prototypes, creating new systems, testing the system and using the system. From the results of the benefit test it can be concluded that functionally the system has produced the output as expected. Thus it can be concluded that the Android-Based Student Daily Activity Report Information System at Adhi Suta Elementary School purbalingga regency can help improve time efficiency in the creation of recap of student activity reports.